Impact of Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) On Rural Labour Markets: An analysis of the impact of MGNREGA on rural labor markets and poverty alleviation in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study has evaluated the differentiating impact of MGNREGA on the extent of fulfillment of the essential entitlements like days of employment, wages and earnings and therefore the extent of coverage of social groups like dalits, adivasis and ladies and poverty alleviation. This study has disaggregated state level data to discern the factors that make a difference to the performance. Also some micro level scenarios are presented supported the reports of focus group discussions (FGDs) within the villages of Andhra Pradesh. There’s growing evidence of a rise in agricultural wages across the country over the amount between 2006-07 and 201112, during which the impact of MGNREGA is considerable. This review has also revealed a steep increase in female agriculture wage and a substantive decline within the male-female wage gap. The look for information on the impact of MGNREGA on agricultural labor markets results in some evidence on labor shortage, changes in wages, mechanization, high season adjustment of labor or adoption of MGNREGA calendar and migration.